Parity and Psychology Analysis with Hyperemesis Gravidarum Incidence in First Trimester Pregnant Women - Lesni Bertaria Rambu Bangi Leli Gadung; Adriana Inya Kendu; Yahaya Jafaru (Open Access Health Scientific Journal, 2022)
Background: Parity and psychological problems are one of the factors that contribute to the high tendency to occur hyperemesis gravidarum as a condition that results in pathology for the mother and the fetus she contains.Methods: The research design is correlational analytic with a cross sectional design approach. The independent variables are parity and psychology, while the dependent variable is the incidence of hyperemesis gravidarum. The population is all pregnant women in the first trimester at the Wairasa Health Center, Central Sumba Regency, East Nusa Tenggara, a sample of 26 respondents using the accidental sampling technique. The data collection technique used a questionnaire.Results: The results of the ordinal regression analysis showed that the Nagelkerke coefficient value of 92.4% means that the independent variable is parity and psychology affects the incidence of hyperemesis gravidarum in general by 92.4% while 7.6% is influenced by other factors that are not included in the model testing.Conclusion: there is a relationship between parity and psychology of pregnant women in the first trimester with the incidence of hyperemesis gravidarum